PAW26 Are the beneficial effects of Botulinum toxin for refractory detrusor overactivity in multiple sclerosis sustained with repeat injections?. Issue 11 (22nd October 2010) - Panicker, J; Khan, S; Game, X; Dalton, C; Gonzales, G; Elneil, S; Hamid, R; Fowler, C
Abstract : Objectives: Intradetrusor injection of Botulinum toxin type A, although not yet licenced, has proven to be highly effective for urge incontinence in multiple sclerosis (MS) due to refractory detrusor overactivity (DO). Here we evaluate the impact of repeat injections on patient reported outcome measures (PROMs) to examine whether benefits are sustained. Methods: People with MS having urodynamically proven refractory DO were injected 300 U Botox© by flexible cystoscopy. Urogenital Distress Inventory (UDI-6), Incontinence Impact Questionnaire (IIQ-7) and EQ-5D were used to record bladder symptoms and quality of life before and 4 weeks after injection. Re-injection was dictated by return of symptoms and urodynamically proven DO. Results: Between 2002 and 2009, 137 patients (106 women, 31 men; mean age 47.8 years (range 24–79)) received detrusor injections. Mean follow-up was 29 months (range 8–80 months). 95 had re-injections (maximum 6 injections, mean 2.9) at inter-injection intervals of median 13 months (IQR 11–16 months). Duration of interval did not change and improvement in PROMs were significant and sustained following each injection. 74% became continent at 4 weeks following treatment. Infection was the commonest side effect (17%). All but two patients required self-catheterisation. Conclusion: Repeat Botulinum toxin injections for refractory DO remains reliably effective in improving bladder symptoms and quality of life when repeated for at least 2 years.